Britt-Marie was here [videorecording (DVD)] - August, Pernilla, 1958-; Haber, Peter, 1952-; Vitali, Vera, 1981- (Cohen Media Group, 2020)
Britt-Marie is a 63-year-old housewife who has just left a 40-year marriage. The small town of Borg has lost its pride, except for the young soccer team, which Britt-Marie now has to coach. This journey will be filled with struggles and challenges, but also warmth and love.